2000
DOI: 10.1046/j.1365-246x.2000.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the magnetotelluric tensor in terms of its invariants

Abstract: Summary The magnetotelluric impedance tensor is defined in terms of seven independent parameters that are invariant under a rotation of the horizontal axes on the surface of the Earth, plus an angle that defines the orientation of the axes of reference. The invariants are algebraically related to but nevertheless different from those recently proposed by Szarka & Menvielle (1997). They have been chosen in such a way as to have clear representations on a Mohr circle diagram and also to reveal geoelectric proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 22 publications
3
162
0
3
Order By: Relevance
“…The data recorded from GHC were corrupted to different degrees by distortion due to different types of geological and man-made noise sources. To deal with noisy data, we used impedance invariants and phase tensor-based techniques for the determination of geoelectric dimensionality and strike directions 21,22 . The basic philosophy of the technique is discussed here briefly.…”
Section: Structure Dimensionality and Geoelectric Strikementioning
confidence: 99%
See 1 more Smart Citation
“…The data recorded from GHC were corrupted to different degrees by distortion due to different types of geological and man-made noise sources. To deal with noisy data, we used impedance invariants and phase tensor-based techniques for the determination of geoelectric dimensionality and strike directions 21,22 . The basic philosophy of the technique is discussed here briefly.…”
Section: Structure Dimensionality and Geoelectric Strikementioning
confidence: 99%
“…Weaver et al 21 have developed dimensionality criteria based on seven rotational invariants (I 1 to I 7 ).…”
Section: Casementioning
confidence: 99%
“…This code calculates strike based on the phase tensor (Caldwell et al, 2004) and impedance tensor invariant (Weaver et al, 2000;Weaver and Lilley, 2004) methods and produces the mean, mode and median for consideration. The strike analysis used has a 90° ambiguity (Thiel, 2008), so the geological strike was used in concert with the strike analysis results to determine the strike of N160°E used for inversion.…”
Section: Discussionmentioning
confidence: 99%
“…There is an appeal in putting both in-phase and quadrature data on the same axes, as demonstrated by Szarka & Menvielle (1997) and Weaver et al (2000), but when showing a full frequency range separate sets of axes are practical. Also at times it is helpful to add axes for Z ′ yx and Z ′ yy as on Fig.…”
Section: The Depiction Of Mt Tensors Using Mohr Diagramsmentioning
confidence: 99%
“…2a that the MT observations can be expressed in terms of seven invariants of rotation. From different sets which are possible, and evident from formal analysis (Szarka & Menvielle, 1997;Weaver et al, 2000), this chapter adopts the invariants shown in Fig. 3.…”
Section: Invariants Of Rotation Of the Measuring Axesmentioning
confidence: 99%